Microteaching Lesson Study of Biology Prospective Teacher to Develop Lesson Plan Design and Teaching Ability - Lukitasari, Marheny; Hasan, Rusdi; Murtafiah, Wasilatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This research aimed to develop the learning tools of the biological subject in high school and the teaching biology ability of the teacher candidates through microteaching-lesson study (MLS). The combination of MLS activities was unfolded in preparing the real learning conditions for prospective teachers who will conduct the field practice in the actual classroom. Data were collected through the observation sheets, interviews, and microteaching scores that represented the students' teaching ability. The data were analyzed descriptively. The results showed that each student capable of designing three learning plans with good and excellent categories. The teaching ability and classroom management of students increase by the three activities that conducted, as can be seen from the mean of first (55,77), the second (71,88), and the third (84,38) practice values. However, the students experienced difficulties in the stages of preparation and implementation concerning the more time needed as well as the more cycle activities. Therefore, the students argued that by the only three cycles of activities they experienced, then the LS would be constrained to introduce in the field practice program at school. The more cycles of MLS and guidance from the lecturer is still needed to make prospective teacher ready to implement LS in their field practice at school.